Identification of cytochrome c oxidase subunit 4 isoform 1 as a positive regulator of influenza virus replication - He, Jun; Huang, Huibin; Li, Bo; Li, Huanan; Zhao, Yue; Li, Yaolan; Ye, Wencai; Qi, Wenbao; Tang, Wei; Wang, Lei (Frontiers in Microbiology, 2022)
Human infection with highly pathogenic H5N1 influenza virus causes severe respiratory diseases. Currently, the drugs against H5N1 are limited to virus-targeted inhibitors. However, drug resistance caused by these inhibitors is becoming a serious threat to global public health. An alternative strategy to reduce the resistance risk is to develop antiviral drugs targeting host cell proteins. In this study, we demonstrated that cytochrome c oxidase subunit 4 isoform 1 (COX41) of host cell plays an important role in H5N1 infection. Overexpression of COX41 promoted viral replication, which was inhibited by silencing or knock-out the expression of COX41 in host cell. The viral ribonucleoproteins (vRNP) were retained in the nucleus after down-regulation of cellular COX41 expression. Strikingly, suppressing the expression of COX41 by lycorine, a small-molecule inhibitor isolated from Amaryllidaceae plants, resulted in the blockage of nuclear export of vRNP and inhibition of viral replication in vitro. In H5N1-infected mice that were treated with lycorine, we observed a reduction of viral titers and inhibition of pathological changes in the lung tissues. Importantly, we did not isolate the resistant virus after culturing the virus with the continuous treatment of lycorine. Collectively, these results provided direct evidence of the positive correlation between cellular COX41 levels and the influenza virus infection. Inhibition of COX41 expression in host cell may serve as a viable approach for anti-influenza therapy.